ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MENYELESAIKAN SOAL-SOAL IPA BERORIENTASI HOTS - Neneng Eliana (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2020)
This study purpose is to determine the critical thinking skills of fourth grade students of 16 Elementary Schools in Panjak, Bengkayang Regency, West Kalimantan Province in solving HOTS oriented science questions. Research subjects totaling 20 people which are students who are in the category have the ability to think critically base on the results of best practice that have been carry out by the teacher. The study was conducted at the beginning of the even semester of the 2019/2020 academic year. The method used in this research is quantitative descriptive. Data collection was carried out using test and interview techniques. Data analysis techniques using descriptive statistical techniques. Based on the results of data analysis, from a maximum score of 5 and at percentage 33,33% each level of thinking, the average score of student’ thinking ability at the C-4 level of thinking (analyzing) reached 4,4 with a percentage of 29,33% and ascore of 3,2 with a percentage of 21,33% at the level of thinking C-5 (evaluating) and C-6 (creating), so to obtain an average total score of 10,8 with an average percentage of 72%, it can be concluded that the critical thinking skills of fourth grade school students 16 Elementary Schools in Panjak, Bengkayang Regency, West Kalimantan Province in solving HOTS oriented science queations is in high category.